Uncertainty about exchange rates affects import prices in the Euro Area - Boris Blagov (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
RWI research shows that monetary policy should take uncertainty about exchange rate fluctuations into account. When aiming at price stability, central banks closely monitor exchange rates. Their level is known to influence prices, since many product components are sourced internationally. An RWI study suggests that central bankers should also take the level of uncertainty about future exchange rates into account when aiming at price stability. The study finds that in the Euro Area, importers bear the main burden of the uncertainty. Mainly affected are countries like Germany, Italy, and the Netherlands, whose industries rely heavily on intermediate goods imports. When uncertainty increases, importers buy less goods to lower the risk. Consequently, prices for intermediate goods fall.
Keywords: 330